The relationship between organizational culture and the transfer of management, functions and roles in the SMES succession: A case study between Hungary and North of Portugal - Costa,José Paulo Machado da (2013)
This article presents the results of a study about the analysis of the relationship between organizational culture and the transfer of management, functions and roles in the succession of SME's. The study is based on a questionnaire directed to the entrepreneurs and managers of SME's. The purpose of this article is to present the results of the last edition of the questionnaire and a comparison between companies in Hungary and in the north of Portugal. The research focuses on the mapping of the state of succession (measured by the distribution of the transferred managerial functions/roles), and examine the influence of the organizational culture. What kind of culture? what kind of role will be passed? About the organizational culture: The empirical development of the Competing Values Framework was completed by Quinn & Rohrbaugh (1981) who simply wanted to find the most important criteria and factors of effective organizational operation. As a starting point, Campbell's list of 39 effectiveness indicators was used. It allowed the comprehensive description of organizational effectiveness. Some of the 39 indicators corresponded; as a result clusters could be created. In the article we conclude with the characterization of the relations between four dimensions of organizational culture: the hierarchy form, the Market type, the clan form of organization and the adhocracy, were defined along two axis (internal/external focus versus stability/flexibility). About the managerial roles, we focus on three management roles that can be find in the literature: the governor, the leader and the manager.